Prevalence of Malocclusion and Related Oral Habits in 5-to 6-year-old Children - dos Santos, Renata Reis [UNESP]; Rodrigues Nayme, Joao Guilherme [UNESP]; Garbin, Artênio José Ísper [UNESP]; Saliba, Nemre Adas [UNESP]; Garbin, Clea Adas Saliba [UNESP]; Moimaz, Suzely Adas Saliba [UNESP] (Quintessence Publishing Co Inc, 2012)
Purpose: To verify the prevalence of malocclusion and the influence of harmful oral habits on deciduous dentition in 5- and 6-year-old children enrolled in Brazilian public elementary schools during 2010.Materials and Methods: Exams were conducted in 1385 children from 56 Brazilian elementary schools using the method recommended by the World Health Organization (WHO) for epidemiological surveys on oral health. Information about the type of arch, social and economic data and harmful oral habits of the children were collected through a structured questionnaire.Results: In relation to canine occlusion, a high prevalence of Class I (74.5%), followed by Class II (19.4%), was found. Among all participants, 22% showed high overjet, 7.8% showed edge-to-edge occlusion and 2.3% showed anterior crossbite. In relation to overbite, 13.2% had short overbite, 14.3% open bite and 16.8% high overbite. The presence of posterior crossbite occurred in 14.6% of children. Maxillae predominantly exhibited the type I arch (67.9%) and mandibles predominantly exhibited type II (51.7%). In relation to harmful oral habits, 43.4% used a pacifier, 84.8% used a bottle and finger sucking was reported by 17.2%.Conclusion: There was a high prevalence of malocclusion associated with oral habits harmful to deciduous dentition.
Keywords: child welfare; dentition; malocclusion; public health dentistry